2016
DOI: 10.1016/j.jvs.2016.01.034
|View full text |Cite
|
Sign up to set email alerts
|

No major difference in outcomes for endovascular aneurysm repair stent grafts placed outside of instructions for use

Abstract: Despite most EVAR patients being treated outside of IFU, there was no difference in outcomes with respect to all-cause mortality or aneurysm-related mortality. In addition, with the exception of perioperative blood transfusions, there was no association between IFU adherence and late-onset rupture, need for reintervention, rates of endoleak, aneurysm sac enlargement, or most other major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 18 publications
2
40
0
2
Order By: Relevance
“…However, recently, it has been reported that there is no difference in the outcomes of EVAR between the patients within and outside of the IFU. [4][5][6]10,11) Beckerman et al concluded that there was no difference in the all-cause mortality or the aneurysm-related mortality despite most EVAR patients being treated outside the IFU. 6) Moreover, aneurysm sac enlargement was identified in 11.7% of overall patients, but no significant difference between patients treated within and outside the IFU (p=0.870).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recently, it has been reported that there is no difference in the outcomes of EVAR between the patients within and outside of the IFU. [4][5][6]10,11) Beckerman et al concluded that there was no difference in the all-cause mortality or the aneurysm-related mortality despite most EVAR patients being treated outside the IFU. 6) Moreover, aneurysm sac enlargement was identified in 11.7% of overall patients, but no significant difference between patients treated within and outside the IFU (p=0.870).…”
Section: Discussionmentioning
confidence: 99%
“…Besides its clinical importance, IFU adherence remains controversial as that is said by the reported studies. [4][5][6] This study aimed to determine how IFU influences the incidence of sac growth and endoleaks post-EVAR and to recognize the computed tomography (CT) features of IFU, which may predict adverse events post-EVAR.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that further study is needed to define concrete benefits related to the use of EVAR in younger patients with longer lifespans. Recent studies have suggested that patients with less anatomically favorable criteria for EVAR may be more likely to experience more long-term complications compared to those with favorable aneurysm anatomy 14,22 , although solid evidence to support this conclusion remains limited and conflicting 23 . Studying younger patients within this “off-IFU” cohort with unfavorable aneurysm anatomy for EVAR may identify a population potentially benefitting from open repair.…”
Section: Discussionmentioning
confidence: 99%
“… 14 However, in a recent report from our group of outcomes in 566 patients, no statistical difference was found in adverse events for patients treated with EVAR outside the IFU. 15 Nevertheless, the long-term durability of our intervention will require close monitoring with clinical evaluation and imaging.…”
Section: Discussionmentioning
confidence: 99%